Determinan Jumlah Uang Beredar dan Tingkat Inflasi di Indonesia Periode 1984-2014 - Luwihadi, Ni Luh Gede Ari; Arka, Sudarsana (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 6, No. 4, April 2017 (pp. 472 - 676), 2017)
The purpose of this study was to analyze the influence of central bank interest rates and US dollar exchange rate to the rate of inflation through the money supply directly and indirectly. The analysis technique used is path analysis. The results of the analysis directly showed interest rates negative and significant effect on the money supply, US dollar exchange rate positive and significant effect on the money supply, interest rates positive and significant impact on the inflation rate, US dollar exchange rate positive and significant impact on inflation and the amount of money circulated no significant effect on the rate of inflation. Indirectly indicate the interest rate and the US dollar exchange rate has no effect on the rate of inflation through the money supply.
Keywords: BI Interest Rate; Rate US Dollar; Inflation Money Supply